Surgical Management of a Hydatid Cyst of the Hepatic Dome Ruptured into the Biliary Tree - Awad, Ali J.; Al-Fayadh, Raysan F. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Hydatid disease remains an important & challenging medical problem.Case report: A62 year old male patient was admitted complaining of upper abdominal discomfort. Six days earlier he suffered from acute pain in the right upper quadrant, mild systemic allergic manifestation, a fever of 38.5oC and chills. He was managed by a new surgical approach of myoplasty of the right hemidiaphragm combined with preoperative decompression of the bile duct by an endoscopic sphincterotomy. A case search identified study describing rupture of a hydatid cyst of the hepatic dome into biliary tract. The incidence of intrabiliary rupture of hepatic hydatid cysts is 25% in patients treated with external surgical drainage for liver hydatid cysts. Postporative external biliary fistula have been reported in 27.5%.Conclusion: this procedure may require less time (because liver mobilization is not necessary) and allows for easier abdominal reoperation in the future. The simplicity of the technique allows for a more reliable alternative to the treatment of the hydatid cyst located over the superior-posterior aspects of the liver.